Cultivar y momento de corte en moha (Setaria italica) para silaje : 1. Producción - Mattera, Juan; Martinez, Emilce Soledad; Barletta, Pablo Fernando; Gallo, Sergio Adrian; Camarasa, Jonatan Nicolás; Cuatrin, Alejandra (Asociación Argentina de Producción Animal (AAPA), 2020)
Publicado en: Revista Argentina de Producción Animal 39 (1) : 116 (Octubre 2019)